Evolutionary Roots and Diversification of the Genus Aeromonas - Sanglas, Ariadna; Albarral, Vicenta; Farfán, Maribel; Lorén, J. G.; Fusté, M. C. (Frontiers in Microbiology, 2017)
Despite the importance of diversification rates in the study of prokaryote evolution, they have not been quantitatively assessed for the majority of microorganism taxa. The investigation of evolutionary patterns in prokaryotes constitutes a challenge due to a very scarce fossil record, limited morphological differentiation and frequently complex taxonomic relationships, which make even species recognition difficult. Although the speciation models and speciation rates in eukaryotes have traditionally been established by analyzing the fossil record data, this is frequently incomplete, and not always available. More recently, several methods based on molecular sequence data have been developed to estimate speciation and extinction rates from phylogenies reconstructed from contemporary taxa. In this work, we determined the divergence time and temporal diversification of the genus Aeromonas by applying these methods widely used with eukaryotic taxa. Our analysis involved 150 Aeromonas strains using the concatenated sequences of two housekeeping genes (approximately 2,000 bp). Dating and diversification model analyses were performed using two different approaches: obtaining the consensus sequence from the concatenated sequences corresponding to all the strains belonging to the same species, or generating the species tree from multiple alignments of each gene. We used BEAST to perform a Bayesian analysis to estimate both the phylogeny and the divergence times. A global molecular clock cannot be assumed for any gene. From the chronograms obtained, we carried out a diversification analysis using several approaches. The results suggest that the genus Aeromonas began to diverge approximately 250 millions of years (Ma) ago. All methods used to determine Aeromonas diversification gave similar results, suggesting that the speciation process in this bacterial genus followed a rate-constant (Yule) diversification model, although there is a small probability that a slight deceleration occurred in recent times. We also determined the constant of diversification (λ) values, which in all cases were very similar, about 0.01 species/Ma, a value clearly lower than those described for different eukaryotes.